Daytime variation in SARS-CoV-2 infection and cytokine production. (September 2021) - Diallo, Aïssatou Bailo; Gay, Laetitia; Coiffard, Benjamin; Leone, Marc; Mezouar, Soraya; Mege, Jean-Louis
Abstract: S. Ray and A. Reddy recently anticipated the implication of circadian rhythm in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which is the causative agent of the coronavirus disease (Covid-19). In addition to its key role in the regulation of biological functions, the circadian rhythm has been suggested as a regulator of viral infections. Specifically, the time of day of infection was found critical for illness progression, as has been reported for influenza, respiratory syncytial and parainfluenza type 3 viruses. We analyzed circadian rhythm implication in SARS-CoV-2 virus infection of isolated human monocytes, key actor cells in Covid-19 disease, from healthy subjects. The circadian gene expression of BMAL1 and CLOCK genes was investigated with q-RTPCR. Monocytes were infected with SARS-CoV-2 virus strain and viral infection was investigated by One-Step qRT-PCR and immunofluorescence. Interleukin (IL)-6, IL-1β and IL-10 levels were also measured in supernatants of infected monocytes. Using Cosinor analysis, we showed that BMAL1 and CLOCK transcripts exhibited circadian rhythm in monocytes with an acrophase and a bathyphase at Circadian Time (CT)6 and CT17. After 48 h, the amount of SARS-CoV-2 virus increased in the monocyte infected at CT6 compared to CT17. The high virus amount at CT6 was associated with significant increased release in IL-6, IL-1β and IL-10 compared to CT17. Our results suggest that time day of SARS-CoV-2 infection affects viral infection and host immune response. They support consideration of circadian rhythm in SARS-CoV-2 disease progression and we propose circadian rhythm as a novel target for managing viral progression. Highlights: Circadian rhythm links to SARS-CoV-2 infection. Day time of SARS-CoV-2 infection modulates viral infection/replication. Day time of SARS-CoV-2 infection impacts on immune response.